Designing an evidence‐based free‐flap pathway in head and neck reconstruction. Issue 2 (27th April 2022) - Mark, Michelle; Eggerstedt, Michael; Urban, Matthew J.; Al‐Khudari, Samer; Smith, Ryan; Revenaugh, Peter
Abstract: Background: The use of autologous free‐tissue transfer is an increasingly utilized tool in the ladder of reconstructive options to preserve and restore function in patients with head and neck cancer. This article focuses on the evidence surrounding perioperative care that optimizes surgical outcomes and describes one tertiary center's approach to standardized free‐flap care. Data Sources: This article examines English literature from PubMed and offers expert opinion on perioperative free‐flap care for head and neck oncology. Conclusion: Free‐flap reconstruction for head and neck cancer is a process that, while individualized for each patient, is best supported by a comprehensive and standardized care pathway. Surgical optimization begins in the preoperative phase and a thoughtful approach to intraprofessional communication and evidence‐based practice is rewarded with improved outcomes.